CHARACTERIZATION OF STAPHYLOCOCCI ISOLATED FROM MAN AND ANIMALS IN NIGERIA (1984)
A combination of physiological, biochemical and molecular characteristics was used in the study of 291 strains of staphylococci isolated from man, goats, sheep, poultry and other animals. Novobiocin-resistant strains were more prevalent amongst the coagulase-negative staphylococci examined. Of the 110 caprine strains of coagulase-negative staphylococci, 91 (87.7 per cent) were novobiocin-resistant. The strains identified to species level were found to be Staphylococcus sciuri, Staphylococcus lentus, Staphylococcus xylosus, Staphylococcus gallinarum, Staphylococcus cohnii and Staphylococcus saprophyticus. Staphylococcus sciuri and Staphylococcus lentus were easily differentiated from other novobiocin-resistant staphylococci by a positive-oxidase reaction. Morphologically, Staphylococcus sciuri and Staphylococcus lentus appeared indistinguishable. Staphylococcus lentus appeared more biochemically active than Staphylococcus sciuri and indeed other coagulase-negative staphylococci isolated from goats with the exception of Staphylococcus gallinarum. Differentiation of Staphylococcus sciuri from Staphylo coccus lentus was facilitated by the inability of several strains of Staphylococcus sciuri to produce acid from melibiose. Novobiocin-resistant staphylococcal species were the only ones isolated from sheep and they had almost identical physiological and biochemical characteristics with those of caprine origin. Staphylococcus gallinarum, a new species of coagulase-negative staphylococci isolated from animals was found amongst the present collection of coagulase-negative staphylococci. Staphylococcus gallinarum resembled Staphylococcus lentus in its acid production from several carbohydrates used but its oxidase-negative reaction was used in its differentiation from Staphylococcus lentus. Staphylococcus gallinarum strains commonly produced acid from fructose, maltose, D-(+)-mannose, D-(-)-ribose, sucrose and D-(+)-trehalose. Most of the novobiocin- resistant, coagulase-negative staphylococci from animals were physiologically active as they produced a variety of extracellular products. Weak desoxyribonuclease activities were commonly found amongst Staphylococcus sciuri and Staphylococcus lentus and the strong reaction produced by Staphylococcus hyicus was found to be of diagnostic use. One strain of Staphylococcus sciuri produced thermostable nuclease and another strain of Staphylococcus lentus produced staphylokinase. Whilst intense protease production was commonly associated with Staphylococcus sciuri and Staphylococcus lentus, none of these strains produced lipolytic effects on egg-yolk medium whilst lipolytic effects were seen in strains of Staphylococcus xylosus and Staphylococcus cohnii. The characteristics of the novobiocin-resistant, coagulase-negative staphylococci isolated from humans did not differ from those of animal strains. The strains of Staphylococcus aureus isolated from humans and animals had similar physiological and biochemical characteristics. The production of hyaluroni-dase and acetoin from glucose was helpful in differentiating Staphylococcus aureus from other coagulase-positive Staphylococcus intermedius and Staphylococcus hyicus strains isolated from various hosts. The strains of Staphylococcus intermedius isolated from a man having a pet dog had similar characteristics as the other strains of Staphylococcus intermedius of canine origin. The human strain of Staphylococcus intermedius produced proteinase, phosphatase, desoxyribonuclease and thermostable nuclease but it failed to hydrolyze Tween 80 and did not produce hyaluronidase and acetoin from glucose. Acid production from a variety of carbohydrates by the human strain of Staphylococcus intermedius was however similar to that of Staphylococcus aureus of human origin but the strain did not produce acid from D-(+)-turanose. In the course of phage typing Staphylococcus aureus strains, a caprine phage was isolated from one strain (UI 150). Three caprine strains of Staphylococcus aureus that were untypable by using the International sets of phages for typing human strains of Staphylococcus aureus were susceptible to this caprine phage Gl. Staphylococcus aureus strains isolated from humans and goats which were susceptible to the phage 80/81 complex had similar antibiograms. Whilst several of the human strains of Staphylococcus aureus were found to be of human biotype, the caprine strains of Staphylococcus aureus belonged to biotype C. Resistance to tetracycline was found in some strains of Staphylococcus aureus of caprine origin whilst a higher percentage of human strains of Staphylococcus aureus produced penicillinase. Sensitivity to the cephalosporins was commonly found amongst all the Staphylococcus aureus strains examined. With human factor sera, all the Staphylococcus aureus strains isolated from humans were serotypable. Of the 14 caprine strains of Staphylococcus aureus examined, 10 were serotypable. Agglutinogens a5, b1, o and h2 were found amongst the Staphylococcus aureus strains of human and animal origins. Two Staphylococcus intermedius strains isolated from humans and dogs were serotypable and they had agglutinogen in common. All the 3 Staphylococcus aureus strains isolated from giant rats (Cricetomys gambianus) were serotypable with a5 and p agglutinogens being common to them. Some isolates were obtained which could not be identified the application of chemotaxonomic and molecular characterization procedures however provided a relationship to some of the newly-described species of staphylococci. Some relatively uncommon teichoic acids were found amongst some strains. A caprine strain of coagulase-positive, staphylococcus had glycerol and glucosamine teichoic acids whilst a strain of coagulase- negative staphylococcus of caprine origin possessed glycerol, glucose, galactose and N-acetylglucosamine teichoic acids. The guanine plus cytosine (G + C) content of the deoxyribonucleic acid (DNA) of some of the strains tested ranged between 32.7 and 34.6 per cent. DNA-DNA hybridization values amongst some of the coagulase- negative staphylococci revealed some relationships to Staphylococcus gallinarum, Staphylococcus lentus and Staphylococcus sciuri.